MENCARI HAKIKAT TUHAN (Menggali Makna Makrifat Al-Ghazali) - mutrofin, mutrofin (IAIN Kediri, 2018)
This article discusses the concept of makrifat Imam Ghazali. In this concept will be explained how a true servant is able to know the nature of God as a whole. Using multiple maqamat in attaining the level of gnosis. As according to Ghazali, that the highest levels of Sufism is makrifat. One of the tools to determine the nature of God by using qalb. Therefore, man should seek knowledge to know God. As Allah says in Hadith Qudsi